ANALISIS KESALAHAN BERBAHASA PADA TULISAN MEDIA LUAR RUANG DI KOTA LANGSA - Tara Astika Bangun (MEDAN MAKNA: Jurnal Ilmu Kebahasaan dan Kesastraan, 2019)
This study aims to describe errors in spelling, diction, and sentence in billboards and plank shops in the area Langsa. The research data was sourced from the writings found on billboards and nameplate stores in Langsa. Source of data which is the object of this study is spelling, diction, and sentence contained on billboards and nameplate stores in Langsa. Data taken from two districts of the five districts in Langsa as samples. Sampling was done by cluster sampling technique. The approach used in this study is theoretical and methodological approaches. The theoretical approach in this research using Indonesian error analysis approach, while the methodological approach used is a qualitative descriptive approach. Data collected by using the method of direct observation, technical notes, and documentation. Analyzing or processing the data of this study using qualitative analysis techniques. The results obtained are still a lot of errors written in outdoor media in Langsa, especially in the district of Langsa town and Langsa Baro are not in accordance with the rules of Indonesian. The most common errors are errors of spelling and word choice (diction).